2015
DOI: 10.1091/mbc.e15-04-0219
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of novel cytoskeletal proteins associated with TbPLK, an essential regulator of cell morphogenesis inTrypanosoma brucei

Abstract: The Trypanosoma brucei polo-like kinase homologue is an essential morphogenic regulator of the parasite's cytoskeleton. A series of proteomic screens identifies potential TbPLK binding partners and substrates and better illustrates how the kinase functions, yielding novel proteins involved in flagellar positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(148 citation statements)
references
References 97 publications
10
138
0
Order By: Relevance
“…S1C), this nomenclature does not sufficiently reflect its localization and function. Although McAllaster et al also showed that RNAi of this protein caused a cytokinesis defect by microscopic inspection, the underlying mechanism was not investigated (23). Our work, however, elucidated the mechanistic role of CIF1 in cytokinesis initiation.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…S1C), this nomenclature does not sufficiently reflect its localization and function. Although McAllaster et al also showed that RNAi of this protein caused a cytokinesis defect by microscopic inspection, the underlying mechanism was not investigated (23). Our work, however, elucidated the mechanistic role of CIF1 in cytokinesis initiation.…”
Section: Discussionmentioning
confidence: 68%
“…S3). CIF1 was also identified as a substrate of TbPLK in a recent study and was named TOEFAZ1 for Tip Of Extending FAZ 1 (23). However, given its additional localization to the cleavage furrow during cytokinesis (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, depletion of four FC constituents individually-FCP1, FC1 (also reported in ref. 22), FCP2/TbKinX1, and FCP4/TbKin15-resulted in a substantial increase in cells with their new flagellum tip not in contact with the old flagellum ( Fig. 7 A and B and SI Appendix, Fig.…”
Section: Immunogold Em Labeling Sublocalizes Proteins To Specific Tipmentioning
confidence: 99%
“…Four proteins were present exclusively at the new flagellum tip of dividing 2F cells. These proteins included Tb927.3.4960, a member of the kinetoplastid-specific kinesin-X1 clade (21), which we named FCP2/TbKinX1; Tb927.8.7540, a previously uncharacterized repetitive kinetoplastid-specific protein, FCP3; Tb927.10.890, a member of the ubiquitous kinesin-15 family (21), FCP4/TbKin15; and Tb927.11.1340, which was recently described as the FC constituent FC1 (22). In addition, two proteins without clear homology outside the Kinetoplastida, Tb927.7.6180, which we named axonemal capping structure 1 (ACS1), and Tb927.11.450, ACS2, were present at tips of both new and old flagella (Fig.…”
Section: Structure Immunoprecipitation Approach Identifies Flagellum mentioning
confidence: 99%
See 1 more Smart Citation